Effect of Bentonite Mudcake on the Interface Between Sandy Clay and Concrete (University of Thi-Qar Journal for Engineering Sciences, 2012)
This paper presents investigation of behavior of bentonite mudcake between soil and concrete. A number of simple shear test have been performed on sandy clay and concrete specimens with and without bentonite mudcake at contact. The constitutive relations such as stress-displacement, dilative and the strength relations have been discussed in details. It was found that thin bentonite mudcake between sandy clay and concrete increases the shear strength, the sliding between soil and concrete in addition to the vertical displacement. The bentonite mudcake has a dual reaction; the upper face interacts with soil and the lower face interacts with concrete, showing different effects.